Hazardous Effects of Lead Acetate on Heavy Proteins of Bactrocera zonata - Rizwan ul Haq (Journal of Basic & Applied Sciences, 2012)
Lead is presume to be an important toxic waste which contaminate the environment, therefore, insects could be influenced easily by the lead., Bactrocera zonata was studied at 48 hours post treatment, under the effects of lead acetate, in different concentrations. It was observed that under the effects of lead abnormalities and malformation were developed in the larvae of flies. Thus these flies could present a useful module for the quick transmission of the environmental hazards due to lead contamination, which exerts a specific physiological and morphological effect on these flies.